George J. Gore's “The Management Internship” - Glueck, William F. (Academy of Management Journal, 1968)
The article presents a response to an earlier article titled ?The Management Internship,? by George J. Gore, which appeared in a previous issue of ?Academy of Management Journal.? The author of this response notes the lack of data to prove Gore's point that the cooperative educational experience is more valuable than a traditional BBA. The author suggests that any university considering a cooperative program evaluate samples of both cooperatively educated and noncooperatively educated students on the basis of knowledge, motivations, etc. and look at longitudinal studies of employment records of both students to gauge employee success.